KONTRIBUSI INFRASTRUKTUR DALAM MENDORONG PERTUMBUHAN EKONOMI INKLUSIF DI INDONESIA - IWAN HARSONO; HIMAWAN SUTANTO; IHSAN ROIS; LULUK FADLIYANTI; BAIQ SARIPTA WIJI MULAWIANI (Universitas Mahasaraswati K. Mataram, 2024)
Poverty, unemployment and inequality are still crucial problems in Indonesia, but they can be resolved through inclusive economic growth. Inclusive economic growth includes equity, equality of opportunity, and protection in market and employment transitions. One factor that can influence inclusive economic growth is infrastructure development. This research aims to analyze the influence of road, electricity, water and telecommunications infrastructure on inclusive economic growth in 34 provinces in Indonesia. Testing was carried out in 34 provinces in Indonesia in the 2015-2021 research year. This research uses a quantitative approach and panel data regression analysis using the Random Effect Model (REM) approach using Eviews 12 software.The results of this research show that road and electricity infrastructure have an insignificant and negative effect, and water and telecommunications infrastructure have a significant and positive effect on inclusive economic growth in Indonesia. Simultaneously, road, electricity, water and telecommunications infrastructure have a significant impact on inclusive economic growth. The implication of this research is that further research is needed regarding the influence of infrastructure on inclusive economic growth in Indonesia and the government needs to develop good quality infrastructure that is evenly distributed throughout all regions in Indonesia, so that inclusive economic growth can be achieved